Study of the blending of petrol with 10% anhydrous ethanol. Evaluation of physicochemical properties - Torres, Jaime; Molina, Daniel; Pinto, Carlos; Rueda, Fernando (CT&F - Ciencia, Tecnología y Futuro, 2002)
This study includes the assessment results for blends of premium and regular gasoline produced in Barrancabermeja's Refinery with 10vol% anhydrous ethanol and concentrations within this range (from 5vol% to 15vol%). The results may allow for a more precise definition of the characteristics for the desired blend. The survey basically focused on the Reid Vapor Pressure (RVP) and the antiknock index (RON+MON/2) properties, in order to determine the variations within these properties when 5vol%, 10vol%, and 15vol% anhydrous ethanol is added to the base fuels. Based on these results, the RVP and antiknock index were determined for the base fuels, blended with 10vol% ethanol, to comply with the quality standards required for Colombian fuels in year 2005. For the adjustment of the base fuel's RVP, a light-vapors, nitrogen-dragging stripper was designed and built. As for the adjustment of the base fuel's antiknock index, blends with straight naphta were made for lower index values, while blends with cracked naphta and high octane alkylate were made for higher index values. Having determined the specifications for base fuels, as required to blend them with 10vol% ethanol and meet the quality standards for Colombian gasoline in year 2005, water tolerance for the blends was estimated at temperature ranges of 273 K to 313 K.